ANALISIS EKONOMI DAN PENGEMBANGAN AGROINDUSTRI SUSU KEDELAI BERBAGAI SKALA USAHA DI WILAYAH KABUPATEN JEMBER - Nanang Agus Winandhoyo; Imam Syafii; Djoko Soejono (University of Jember, 2015)
Soy milk agroindustry is one of soy commodity processing with the aim to get added value by processingsoy milk product. This research aimed to determine: (1) the soy raw material stock, (2) the soy milk agroindustry income, (3) the efficiency of soy milk agroindustry production cost, (4) the value added of soy milk agroindustry, and (5) the development prospect of soy milk agroindustry. Research method used is descriptive and analysis methods. The sampling method using purposive sampling method. The result of this study showed that (1) the soy milk agroindustry have a total raw material cost which was bigger than EOQ total cost. (2) The income of soy milk agroindustry for home scale was Rp 15.987,95; Rp167.748,31 for small scale; and Rp 1.909.549,09 for medium scale industry.(3) The soy milk agroindustry production cost were efficient. (4) the value added of soy milk agroindustry in various scale are have been able to give the positive values.(5) the SWOT analysis result of soy milk agroindustry in Jember area showed that the industry were in white area (strengths - opportunities) which showed the industry have a prospect to be developed.Keywords : Soy milk Agroindustry, raw material stock , income, efficiency, Value added, SWOT